Mapping of ITB bachelor of visual arts students’ theses from 2005 to 2022 based on premodern themes - Almira Belinda Zainsjah; Ira Adriati; Nuning Yanti Damayanti (Cogent Arts & Humanities)
We often use an ambiguous term like premodern to discuss various topics that occurred before the modern era. Despite its familiar use, no one has attempted to classify research on premodern themes. This research tries to map the topics that can be discussed under the premodern umbrella by classifying theses written by Institut Teknologi Bandung (ITB) visual art undergraduate students. As a qualitative research, this paper focus on mapping theses from 2005 to 2022 due to changes in the research template, particularly the movement of the theory section to Chapter II, and the absence of premodern research in 1995–2004. The method used in this paper is initial coding to select and reduce data by connecting them with premodern definitions based on dictionaries, and axial coding to look for categories that can connect all the codes in the initial coding. Initial coding is specifically used on research titles to determine the tendencies and frequency of premodern research each year, while axial coding is used on research problems from the selected period so we can find out more about research interests in this period. The results of our analysis show that there are 3 scopes of premodern research in ITB’s bachelor of visual art, namely based on time periods, research on traditional artifacts (regardless of the period), and research that meets these two requirements. Moreover, by disregarding its period limitation, the problems examined in premodern research can be divided into three large categories under cultural traits, such as ideas, activities and artifacts.